Antecedents of customer retention on the network Solinca Health & Fitness Clubs: a look at the last 5 years of fitness in Portugal - Gonçalves, Celina (2020)
Customer retention is critical in the fitness industry because of its impact on the profitability of organizations. For this reason, several studies have focused on understanding and explaining their antecedents. Thus, the objective of this study is to understand the history of retention of fitness members in Portugal and its evolution over the last five years, specifically in the Solinca Health & Fitness Clubs network. The methodology was based on literature review, based on articles on fitness retention in Portugal, published from 2012 to 2017, and peer-reviewed. The research was carried out in the B-on databases and university repositories and included the analysis of titles and keywords of the publications, considering the terms related to fitness retention. In the scope of this research, ten articles were found, of which three were eliminated, prior to 2012. Thus, seven articles were considered in the triage, two PhD theses and thirteen publications of national and international congresses. The results under analysis are related to data from one of the largest fitness networks in Portugal, Solinca Health & Fitness Clubs, and the analysis of this article rests specifically on the retention of customers of this brand of gymnasiums.